1998
DOI: 10.1055/s-2007-978921
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Simmondsin and Cholecystokinin on Metabolism, Brown Adipose Tissue and the Pancreas in Food-Restricted Rats

Abstract: In this study, we investigated the analogies between the physiological effects of simmondsin, a satiety-inducing glycoside extracted from jojoba seeds, and the gastro-intestinal satiation peptide, cholecystokinin. The effects of intraperitoneal injection of the biological active CCK-octapeptide on the pancreas, interscapular brown adipose tissue, growth performance and energy metabolism in normal-fed, severely food intake-restricted (50 % of normal food intake) or moderately food intake-restricted (65 % of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…As shown in Table (9) serum T3 and T4 levels showed numerical significant (P<0.05) increase for T4 in group fed R1 as compared with the other group. These results coincide with those reported previously by Amouts et al (1993) in poultry and by Cokelaere et al (1993) and Flo et al (1998 and in rats. The same authors recorded that simmondsin reduces the body weight due to its effect on thyroid hormones and insulin.…”
Section: Itemsupporting
confidence: 93%
“…As shown in Table (9) serum T3 and T4 levels showed numerical significant (P<0.05) increase for T4 in group fed R1 as compared with the other group. These results coincide with those reported previously by Amouts et al (1993) in poultry and by Cokelaere et al (1993) and Flo et al (1998 and in rats. The same authors recorded that simmondsin reduces the body weight due to its effect on thyroid hormones and insulin.…”
Section: Itemsupporting
confidence: 93%
“…Therefore it was suggested that simmondsin displays its effect by interfering with the endogenous cholecystokinin (CCK) system. Comparison of some physiological parameters in the rat after chronic administration of CCK or simmondsin revealed analogies in pancreatic and brown adipose tissue stimulation and in metabolic parameters (Flo et al, 1998b), thereby supporting the involvement of CCK in the action of simmondsin. Since simmondsin itself does not directly activate the CCK-A receptors (Cokelaere et al, 1995b), and since the presence of simmondsin in the proximal gut seems to be crucial for its anorexigenic effect (Flo et al, 1997), it was hypothesized that simmondsin acts on the proximal gut to stimulate the production or liberation of CCK and thus to reduce food intake.…”
Section: Introductionmentioning
confidence: 65%
“…It was shown that simmondsin, or 2-(cyanomethylene)-3 hydroxy 4,5 dimethoxy cyclohexyl -D glucoside (Elliger et al, 1973), is the most important anorexigen for rats in extract from the jojoba meal (Cokelaere et al, 1996;Flo et al, 1998a). In view of the great interest in control of body weight in humans and even pet animals, experiments were performed to unravel the mechanism by which jojoba meal and more specifically simmondsin reduces food intake.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism involves the effect of simmondsin on the CCK system. The fact that simmondsin treatment interferes with the endogenous CCK system is well documented (Cokelaere et al 1995a,b;Flo et al 1998). Both CCK and simmondsin induce food intake reduction, at least partially, through stimulation of the vagus nerve (Joyner et al 1993; G Flo, M Van Boven, S Vermaut, P Daenens, E Decuypere and M Cokelaere, unpublished results).…”
Section: Discussionmentioning
confidence: 88%
“…Since its effect is much more pronounced in non-fasted rats than in fasted rats, it was postulated that simmondsin causes food intake reduction by inducing satiety and not aversion (Cokelaere et al 1995a;G Flo, M Van Boven, S Vermaut, P Daenens, E Decuypere and M Cokelaere, unpublished results). The physiological effects of chronic simmondsin administration are identical to those seen with chronic cholecystokinin (CCK) administration (Flo et al 1998), and administration of devazepide, a potent peripheral CCK receptor blocker, abolishes the food intake-reducing activity of simmondsin (Cokelaere et al 1995b). Moreover, the anorexic effect of simmondsin is, at least partly, vagally mediated (G Flo, M Van Boven, S Vermaut, P Daenens, E Decuypere and M Cokelaere, unpublished results).…”
Section: Simmondsin: Food Intake: Heat Productionmentioning
confidence: 82%